5y+18=-y-6

Simple and best practice solution for 5y+18=-y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y+18=-y-6 equation:


Simplifying
5y + 18 = -1y + -6

Reorder the terms:
18 + 5y = -1y + -6

Reorder the terms:
18 + 5y = -6 + -1y

Solving
18 + 5y = -6 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
18 + 5y + y = -6 + -1y + y

Combine like terms: 5y + y = 6y
18 + 6y = -6 + -1y + y

Combine like terms: -1y + y = 0
18 + 6y = -6 + 0
18 + 6y = -6

Add '-18' to each side of the equation.
18 + -18 + 6y = -6 + -18

Combine like terms: 18 + -18 = 0
0 + 6y = -6 + -18
6y = -6 + -18

Combine like terms: -6 + -18 = -24
6y = -24

Divide each side by '6'.
y = -4

Simplifying
y = -4

See similar equations:

| 120=x(x^2/20) | | 14x+5=-7+19x | | 3(x-5)+2(3x+11)=45 | | 3(2r-3)=0.2r+0.9 | | 12+6y=-8y-2 | | 5x^2+16+3=0 | | -3(4x+3)+4(6x+1)=41 | | 2x+17=8(x-1)+1 | | y=0.5x+0.5 | | -17-2x=16-x | | (9a^-6b^2)/(17a^6b^-8) | | 1/3y+1/4=15/12-1/4 | | 3/4x7/12= | | 9x^2+4x-81=0 | | 3xsquared+11x=4 | | -4+.666y=.5y-5 | | 8/93/21 | | x=3x-127 | | 20=q | | 0.14y-1.6+3.12y+3.6= | | -6-3(2k-4)=18 | | a/3=-0.2 | | (9x+5)-(12x+7)= | | 3.4(2x+5)=-.2(2x+5) | | 12.3x=27.06 | | .5x+5=.33333333333333333333333333333333x+7 | | 4x^2(x-1)=0 | | 418=22x | | 1/4÷2/7= | | 28-4x/3=x | | 6-x=d | | 2x-44=-3 |

Equations solver categories